Female devotion and textile imagery in Medieval English literature - MCKAY, ANNA (D S BREWER, 2024)
Uncovers the female voices, lived experiences, and spiritual insights encoded by the imagery of textiles in the Middle Ages. For millennia, women have spoken and read through cloth. The literature and art of the Middle Ages are replete with images of women working cloth, wielding spindles, distaffs, and needles, or sitting at their looms. Yet they have been little explored. Drawing upon the burgeoning field of medieval textile studies, as well as contemporary theories of gender, materiality, and eco-criticism, this study illustrates how textiles provide a hermeneutical alternative to the patriarchally-dominated written word. It puts forward the argument that women's devotion during this period was a "fabricated" phenomenon, a mode of spirituality and religious exegesis expressed, devised, and practised through cloth. Centred on four icons of female devotion (Eve, Mary, St Veronica, and - of course - Christ), the book explores a broad range of narratives from across the rich tapestry of medieval English literature, from the fields of Piers Plowman to the late medieval Morte D'arthur; the devotions of Margery Kempe to the visionary experiences of Julian of Norwich; Gervase of Tilbury's fabulous Otia Imperialia to the anchoritic guidance literature of the Middle Ages; and the innumerable (and oft-forgotten) lives of Christ, prayers, legends, and miracle tales in between.